Two nitazoxanide-based quadruple regimens for eradication of Helicobacter pylori infection: a single-center randomized controlled trial - Amro M Hassan; Khaled Eid; Khaled A.M Eliwa; Muhammad Abdel-Gawad (Wolters Kluwer Medknow Publications, 2022)
Background and aim Eradication of Helicobacter pylori becomes an ongoing challenge worldwide because eradication rates of H. pylori are declining to less than 60% in some countries. As there is no acceptable definite long-standing used therapeutic regimen for H. pylori, clinicians are doing their best to find new regimens to improve eradication rates of H. pylori. Nitazoxanid and fluoroquinolones, including moxifloxacin and levofloxacin, have been used in treatment of H. pylori. The study aimed to assess and compare the efficacy of two nitazoxanide-based quadruple regimens in treatment of patients infected with H. pylori. Patients and methods This prospective randomized controlled trial was conducted on 100 patients diagnosed to be infected by H. pylori by stool antigen test (one-step H. pylori Antigen test Device). They were randomized into two groups: group 1: 50 patients were treated for 14 days with quadruple therapy, including nitazoxanide, moxifloxacin, omeprazole, and doxycycline; and group 2: 50 patients were treated for 14 days with quadruple therapy, including nitazoxanide, levofloxacin, omeprazole, and doxycycline. Eradication of H. pylori was assessed 4 weeks after the end of treatment by stool antigen test (one-step H. pylori Antigen test Device). Results Eradication rate of H. pylori infection was higher in patients treated with nitazoxanide-moxifloxacin-based quadruple therapy 37 (74%) than in patients treated with nitazoxanide-levofloxacin-based quadruple therapy 32 (64%), but there were no significant differences between the studied groups with P value (P<0.28). By subgroup analysis of eradication rate among anemic and nonanemic patients treated by nitazoxanide-moxifloxacin and nitazoxanide-levofloxacin-based quadruple therapy, we found that eradication rate was higher in anemic patients 88% and 80% than nonanemic patients 60% and 45%, with significant P values 0.02 and 0.01, respectively. Conclusions Use of moxifloxacin instead of levofloxacin in the nitazoxanide-based quadruple regimen improves eradication therapy of H. pylori.